A low-loss powder metallurgy magnetic core material and preparation method thereof

Through a specific ratio of rare earth powder metallurgical magnetic core material preparation technology, combined with tea polyphenol chitosan nanoparticles and rosin-based polyimide, the problems of high magnetic loss and low saturation flux density of existing magnetic core materials are solved, and the problem of high magnetic loss and low saturation flux density is achieved. It has low loss and high saturation flux density magnetic core materials, suitable for high frequency and high power fields.

CN118398318BActive Publication Date: 2025-01-07YANGZHOU GUOGUANG NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410552874.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2025-01-07
Estimated Expiration
2044-05-07

AI Technical Summary

Technical Problem

In the field of high frequency and high power, existing magnetic core materials have problems such as high magnetic loss, low saturation flux density and poor comprehensive magnetic performance, which limits their application range.

Method used

Rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, indium powder, iridium powder, silver powder, non-metallic components, nano additives and iron powder are mixed in a specific proportion, and are then mixed by ball milling, pre-firing and pressing. , sintering and heat treatment steps to prepare low-loss powder metallurgical core materials, and use additives such as tea polyphenol chitosan nanoparticles and soluble rosin-based polyimide to improve component compatibility and performance.

Benefits of technology

It significantly reduces magnetic loss, improves saturated magnetic flux density, and improves comprehensive magnetic performance. It is suitable for applications in high-frequency and high-power fields. It has simple process, convenient control and little environmental impact, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A low-loss powder metallurgy magnetic core material and a preparation method thereof, relating to the technical field of magnetic core materials, is made of the following components by weight percentage: rare earth powder 0.1wt%-0.3wt%, manganese powder 3wt%-5wt%, cobalt powder 1wt%-2wt%, nickel powder 6wt%-10wt%, chromium powder 0.8wt%-1.5wt%, aluminum powder 0.05wt%-0.1wt%, copper powder 0.5wt%-1.2wt%, indium powder 0.03wt%-0.05wt%, iridium powder 0.01wt%-0.03wt%, silver powder 0.001wt%-0.003wt%, non-metallic components 0.1wt%-0.5wt%, other metal components 0.03wt%-0.06wt%, nano additives 0.08wt%-0.12wt%, and the remainder is iron powder. The material has low magnetic loss, large saturation magnetic flux density, and good comprehensive magnetic properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic core materials, and in particular to a low-loss powder metallurgy magnetic core material and a preparation method thereof. Background Art

[0002] Magnetic cores are essential electronic materials for miniaturization and light weight of products such as inductors, filters, pulse transformers, etc. in electronic equipment such as program-controlled communications, digital technology, and network communications. With the rapid advancement of electronic technology, higher and higher requirements are placed on the performance of corresponding magnetic core materials. In order to meet the material requirements for magnetic core miniaturization and high DC superposition characteristics in emerging fields such as aerospace communications, new energy vehicles, clean energy, LED green lighting, and portable electronic devices, it is imperative to develop magnetic core materials with low loss and high saturation flux density.

[0003] At present, the magnetic core materials on the market are usually made by powder metallurgy, which have more or less defects such as poor comprehensive magnetic properties, large magnetic loss, low saturation magnetic flux density and Curie temperature, which seriously hinder their application in high-frequency and high-power fields. In order to solve the above problems, the Chinese invention patent with authorization announcement number CN110335732B discloses a manganese-zinc body magnetic core with high saturation magnetic flux density and its preparation method, which belongs to the field of magnetic material technology. The preparation method of the manganese-zinc ferrite magnetic core uses manganese powder, zinc oxide powder, silicon dioxide, calcium oxide, vanadium pentoxide and iron powder as raw materials; first, manganese powder, zinc oxide powder, and iron powder are subjected to synthesis reaction with hydrochloric acid and liquid ammonia, and then, after pre-sintering, doping ball milling, pressing molding, sintering treatment and cutting air gap treatment, a manganese-zinc ferrite magnetic core can be obtained. The invention uses iron powder, manganese powder and zinc oxide powder as initial raw materials, and successively conducts synthesis reaction with hydrochloric acid and liquid ammonia and pre-sintering treatment on iron powder, manganese powder and zinc oxide powder, so as to obtain iron trioxide, manganese oxide and zinc oxide with less impurities, so that the physical and chemical reactions of each component can be uniform in the subsequent sintering treatment, so as to achieve the purpose of reducing the porosity of the magnetic core, increasing the magnetic core density and increasing the saturation magnetic flux density. However, the power loss of the magnetic core material still needs to be further improved.

[0004] It can be seen that the development of a low-loss powder metallurgy core material with low magnetic loss, high saturation flux density and good comprehensive magnetic properties and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the core material field. Summary of the invention

[0005] In view of the above problems, the object of the present invention is to provide a low-loss powder metallurgy core material with low magnetic loss, high saturation magnetic flux density and good comprehensive magnetic properties and a preparation method thereof.

[0006] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: a low-loss powder metallurgy magnetic core material is made of the following components in weight percentage: rare earth powder 0.1wt%-0.3wt%, manganese powder 3wt%-5wt%, cobalt powder 1wt%-2wt%, nickel powder 6wt%-10wt%, chromium powder 0.8wt%-1.5wt%, aluminum powder 0.05wt%-0.1wt%, copper powder 0.5wt%-1.2wt%, indium powder 0.03wt%-0.05wt%, iridium powder 0.01wt%-0.03wt%, silver powder 0.001wt%-0.003wt%, non-metallic components 0.1wt%-0.5wt%, other metal components 0.03wt%-0.06wt%, nano additives 0.08wt%-0.12wt%, and the balance is iron powder.

[0007] Preferably, the nano additive is a mixture of nano ferrosoferric oxide, nano neodymium oxide, nano niobium oxide and nano yttrium oxide in a mass ratio of (3-5):0.5:(0.8-1.2):1.

[0008] Preferably, the particle size of the nano additive is 10-80 nm.

[0009] Preferably, the other metal component is at least one of titanium powder, vanadium powder, tantalum powder, bismuth powder, rhenium powder, beryllium powder and cesium powder.

[0010] Preferably, the non-metallic component is a mixture of Si, B, and N in a mass ratio of (5-8):0.3:(0.1-0.4).

[0011] Preferably, the rare earth powder is at least one of Gd powder, Tb powder, Dy powder and Er powder.

[0012] Preferably, the particle size of the rare earth powder is 1300-1600 mesh; the particle size of the manganese powder is 1200-1500 mesh; the particle size of the cobalt powder is 1300-1600 mesh; the particle size of the nickel powder is 1500-2000 mesh; the particle size of the chromium powder is 1200-1600 mesh; the particle size of the aluminum powder is 1200-1500 mesh; the particle size of the copper powder is 1100-1400 mesh; the particle size of the indium powder is 1100-1400 mesh; the particle size of the iridium powder is 1200-1500 mesh; the particle size of the silver powder is 1000-1300 mesh; the particle size of the non-metallic component is 1000-1300 mesh; and the particle size of the other metal components is 1000-1300 mesh.

[0013] Preferably, the iron powder is carbonyl iron powder, and the carbon content of the carbonyl iron powder is less than 0.03wt.%; the particle size of the iron powder is 1200-1600 mesh.

[0014] Preferably, the preparation components of the low-loss powder metallurgy magnetic core material also include: 0.1wt%-0.3wt% of tea polyphenol chitosan nanoparticles, 0.8wt%-1.2wt% of soluble rosin-based polyimide, and 0.1wt%-0.3wt% of 1,3,5-triglycidyl-S-triazinetrione.

[0015] Preferably, there is no special requirement for the source of the tea polyphenol chitosan nanoparticles. In one embodiment of the present invention, the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of Chinese invention patent application number 201110037219.5.

[0016] Preferably, there is no special requirement for the source of the soluble rosin-based polyimide. In one embodiment of the present invention, the soluble rosin-based polyimide is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN1102690414B.

[0017] Another object of the present invention is to provide a method for preparing the low-loss powder metallurgy magnetic core material, comprising the following steps:

[0018] Step S1, mixing rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, copper powder, indium powder, iridium powder, silver powder, non-metallic components, other metal components, nano additives and iron powder according to weight percentage, and ball milling at a speed of 250-300rpm for 2-5h; then pre-calcining at 700-750°C for 1-3h under nitrogen atmosphere protection, and then heating to 930-960°C for 2-4h to obtain a pre-calcined material;

[0019] Step S2, mixing the pre-sintered material, tea polyphenol chitosan nanoparticles, soluble rosin-based polyimide and 1,3,5-triglycidyl-S-triazinetrione, and ball milling at a rotation speed of 250-300 rpm for 8-15 hours; pressing into a blank, and performing heat treatment after secondary sintering to obtain a low-loss powder metallurgy magnetic core material.

[0020] Preferably, the pressing die pressure in step S2 is 280-420 MPa, and the pressure is maintained for 8-15 seconds.

[0021] Preferably, the secondary sintering in step S2 is carried out at a temperature of 1230-1380° C. for a time of 4-6 hours, and the sintering vacuum is maintained at 0.01-0.06 Pa.

[0022] Preferably, the heat treatment in step S2 includes annealing and tempering; the tempering temperature is 210°C to 350°C, and the time is 1 to 3 hours; the annealing includes two-stage annealing, the first stage annealing temperature is 190-250°C, and the insulation time is 25-65 minutes; the second stage annealing temperature is 750-850°C, and the insulation time is 1-2 hours.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The method for preparing low-loss powder metallurgy magnetic core materials disclosed in the present invention has a simple preparation process, convenient operation and control, no need for special equipment and production lines, low capital investment, low labor intensity, small impact on the environment, high preparation efficiency and finished product qualification rate, is suitable for continuous large-scale production, and has high promotion and application value.

[0025] (2) The low-loss powder metallurgy magnetic core material disclosed in the present invention is made of the following components in weight percentage: rare earth powder 0.1wt%-0.3wt%, manganese powder 3wt%-5wt%, cobalt powder 1wt%-2wt%, nickel powder 6wt%-10wt%, chromium powder 0.8wt%-1.5wt%, aluminum powder 0.05wt%-0.1wt%, copper powder 0.5wt%-1.2wt%, indium powder 0.03wt%-0.05wt%, iridium powder 0.01wt%-0.03wt%, silver powder 0.001wt%-0.003wt%, non-metallic components 0.1wt%-0.5wt%, other metal components 0.03wt%-0.06wt%, nano additives 0.08wt%-0.12wt%, and the balance is iron powder. Through the mutual cooperation and joint action of various components, the manufactured magnetic core material has low magnetic loss, high saturation magnetic flux density and good comprehensive magnetic properties.

[0026] (3) The low-loss powder metallurgy magnetic core material disclosed in the present invention, the preparation components of the low-loss powder metallurgy magnetic core material also include: 0.1wt%-0.3wt% of tea polyphenol chitosan nanoparticles, 0.8wt%-1.2wt% of soluble rosin-based polyimide, and 0.1wt%-0.3wt% of 1,3,5-triglycidyl-S-triazinetrione. Through their mutual coordination, the compatibility between the components is better, thereby improving the performance stability and comprehensive performance of the final product; at the same time, it can also effectively improve the comprehensive magnetic properties and reduce losses.

[0027] (4) The low-loss powder metallurgy magnetic core material disclosed in the present invention has low magnetic loss, high saturation magnetic flux density and good comprehensive magnetic properties through reasonable selection of preparation process parameters. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0029] Example 1

[0030] A low-loss powder metallurgy magnetic core material is made of the following components in percentage by weight: 0.1wt% rare earth powder, 3wt% manganese powder, 1wt% cobalt powder, 6wt% nickel powder, 0.8wt% chromium powder, 0.05wt% aluminum powder, 0.5wt% copper powder, 0.03wt% indium powder, 0.01wt% iridium powder, 0.001wt% silver powder, 0.1wt% non-metallic component, 0.03wt% other metal component, 0.08wt% nano additive, and the balance is iron powder.

[0031] The nano-additive is a mixture of nano-ferroferric oxide, nano-neodymium oxide, nano-niobium oxide, and nano-yttrium oxide in a mass ratio of 3:0.5:0.8:1; the particle size of the nano-additive is 10nm; the other metal components are titanium powder; the non-metallic components are Si, B, and N mixed in a mass ratio of 5:0.3:0.1; and the rare earth powder is Gd powder.

[0032] The particle size of the rare earth powder is 1300 mesh; the particle size of the manganese powder is 1200 mesh; the particle size of the cobalt powder is 1300 mesh; the particle size of the nickel powder is 1500 mesh; the particle size of the chromium powder is 1200 mesh; the particle size of the aluminum powder is 1200 mesh; the particle size of the copper powder is 1100 mesh; the particle size of the indium powder is 1100 mesh; the particle size of the iridium powder is 1200 mesh; the particle size of the silver powder is 1000 mesh; the particle size of the non-metallic component is 1000 mesh; and the particle size of the other metal components is 1000 mesh.

[0033] The iron powder is carbonyl iron powder, and the carbon content of the carbonyl iron powder is less than 0.03wt.%; the particle size of the iron powder is 1200 meshes.

[0034] The preparation components of the low-loss powder metallurgy magnetic core material also include: 0.1wt% of tea polyphenol chitosan nanoparticles, 0.8wt% of soluble rosin-based polyimide, and 0.1wt% of 1,3,5-triglycidyl-S-triazinetrione; the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent with application number 201110037219.5; the soluble rosin-based polyimide is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN1102690414B.

[0035] A method for preparing the low-loss powder metallurgy magnetic core material comprises the following steps:

[0036] Step S1, rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, copper powder, indium powder, iridium powder, silver powder, non-metallic components, other metal components, nano additives and iron powder are mixed according to weight percentage, and ball milled at a speed of 250 rpm for 2 hours; then pre-calcined at 700° C. for 1 hour under the protection of nitrogen atmosphere, and then heated to 930° C. and pre-calcined for 2 hours to obtain a pre-calcined material;

[0037] Step S2, mixing the pre-sintered material, tea polyphenol chitosan nanoparticles, soluble rosin-based polyimide and 1,3,5-triglycidyl-S-triazinetrione, and ball milling at a rotation speed of 250 rpm for 8 hours; pressing into a blank, and after secondary sintering, heat treatment to obtain a low-loss powder metallurgy magnetic core material.

[0038] The pressing die pressure in step S2 is 280 MPa, and the pressure is maintained for 8 seconds; the secondary sintering temperature in step S2 is 1230° C., the time is 4 hours, and the sintering vacuum is maintained at 0.01 Pa.

[0039] The heat treatment in step S2 includes annealing and tempering; the tempering temperature is 210°C and the time is 1 hour; the annealing includes two-stage annealing, the first stage annealing temperature is 190°C and the temperature is kept for 25 minutes; the second stage annealing temperature is 750°C and the temperature is kept for 1 hour.

[0040] Example 2

[0041] A low-loss powder metallurgy magnetic core material is made of the following components in percentage by weight: 0.15wt% rare earth powder, 3.5wt% manganese powder, 1.2wt% cobalt powder, 7wt% nickel powder, 1wt% chromium powder, 0.06wt% aluminum powder, 0.7wt% copper powder, 0.035wt% indium powder, 0.015wt% iridium powder, 0.0015wt% silver powder, 0.2wt% non-metallic component, 0.04wt% other metal component, 0.09wt% nano additive, and the balance is iron powder.

[0042] The nano-additive is a mixture of nano-ferroferric oxide, nano-neodymium oxide, nano-niobium oxide and nano-yttrium oxide in a mass ratio of 3.5:0.5:0.9:1; the particle size of the nano-additive is 20nm; the other metal component is vanadium powder; the non-metallic component is a mixture of Si, B and N in a mass ratio of 6:0.3:0.2; and the rare earth powder is Tb powder.

[0043] The particle size of the rare earth powder is 1400 mesh; the particle size of the manganese powder is 1300 mesh; the particle size of the cobalt powder is 1400 mesh; the particle size of the nickel powder is 1600 mesh; the particle size of the chromium powder is 1300 mesh; the particle size of the aluminum powder is 1300 mesh; the particle size of the copper powder is 1200 mesh; the particle size of the indium powder is 1200 mesh; the particle size of the iridium powder is 1300 mesh; the particle size of the silver powder is 1100 mesh; the particle size of the non-metallic component is 1100 mesh; and the particle size of the other metal components is 1100 mesh.

[0044] The iron powder is carbonyl iron powder, and the carbon content of the carbonyl iron powder is less than 0.03wt.%; the particle size of the iron powder is 1300 meshes.

[0045] The preparation components of the low-loss powder metallurgy magnetic core material also include: 0.15wt% of tea polyphenol chitosan nanoparticles, 0.9wt% of soluble rosin-based polyimide, and 0.15wt% of 1,3,5-triglycidyl-S-triazinetrione; the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent with application number 201110037219.5; the soluble rosin-based polyimide is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN1102690414B.

[0046] A method for preparing the low-loss powder metallurgy magnetic core material comprises the following steps:

[0047] Step S1, mixing rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, copper powder, indium powder, iridium powder, silver powder, non-metallic components, other metal components, nano additives and iron powder according to weight percentage, and ball milling for 3 hours at a speed of 260 rpm; then pre-calcining at 720° C. for 1.5 hours under the protection of nitrogen atmosphere, and then heating to 940° C. for pre-calcining for 2.5 hours to obtain a pre-calcined material;

[0048] Step S2, mixing the pre-sintered material, tea polyphenol chitosan nanoparticles, soluble rosin-based polyimide and 1,3,5-triglycidyl-S-triazinetrione, and ball milling at a rotation speed of 270 rpm for 10 hours; pressing into a blank, and after secondary sintering, heat treatment to obtain a low-loss powder metallurgy magnetic core material.

[0049] The pressing die pressure in step S2 is 310 MPa, and the pressure is maintained for 10 seconds; the secondary sintering temperature in step S2 is 1260° C., the time is 4.5 hours, and the sintering vacuum is maintained at 0.02 Pa.

[0050] The heat treatment in step S2 includes annealing and tempering; the tempering temperature is 240°C and the time is 1.5 hours; the annealing includes two-stage annealing, the first stage annealing temperature is 210°C and the temperature is kept for 35 minutes; the second stage annealing temperature is 770°C and the temperature is kept for 1.2 hours.

[0051] Example 3

[0052] A low-loss powder metallurgy magnetic core material is made of the following components in percentage by weight: 0.2wt% rare earth powder, 4wt% manganese powder, 1.5wt% cobalt powder, 8wt% nickel powder, 1.2wt% chromium powder, 0.07wt% aluminum powder, 0.9wt% copper powder, 0.04wt% indium powder, 0.02wt% iridium powder, 0.002wt% silver powder, 0.35wt% non-metallic component, 0.045wt% other metal component, 0.1wt% nano additive, and the balance is iron powder.

[0053] The nano-additive is a mixture of nano-ferroferric oxide, nano-neodymium oxide, nano-niobium oxide, and nano-yttrium oxide in a mass ratio of 4:0.5:1:1; the particle size of the nano-additive is 60nm; the other metal components are tantalum powder; the non-metallic components are Si, B, and N mixed in a mass ratio of 6.5:0.3:0.25; and the rare earth powder is Dy powder.

[0054] The particle size of the rare earth powder is 1450 mesh; the particle size of the manganese powder is 1350 mesh; the particle size of the cobalt powder is 1450 mesh; the particle size of the nickel powder is 1800 mesh; the particle size of the chromium powder is 1400 mesh; the particle size of the aluminum powder is 1350 mesh; the particle size of the copper powder is 1250 mesh; the particle size of the indium powder is 1300 mesh; the particle size of the iridium powder is 1350 mesh; the particle size of the silver powder is 1200 mesh; the particle size of the non-metallic component is 1150 mesh; and the particle size of the other metal components is 1200 mesh.

[0055] The iron powder is carbonyl iron powder, and the carbon content of the carbonyl iron powder is less than 0.03wt.%; the particle size of the iron powder is 1400 meshes.

[0056] The preparation components of the low-loss powder metallurgy magnetic core material also include: 0.2wt% of tea polyphenol chitosan nanoparticles, 1wt% of soluble rosin-based polyimide, and 0.2wt% of 1,3,5-triglycidyl-S-triazinetrione; the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent with application number 201110037219.5; the soluble rosin-based polyimide is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN1102690414B.

[0057] A method for preparing the low-loss powder metallurgy magnetic core material comprises the following steps:

[0058] Step S1, mixing rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, copper powder, indium powder, iridium powder, silver powder, non-metallic components, other metal components, nano additives and iron powder according to weight percentage, and ball milling for 3.5 hours at a rotation speed of 280 rpm; then pre-calcining at 730° C. for 2 hours under the protection of nitrogen atmosphere, and then heating to 945° C. and pre-calcining for 3 hours to obtain a pre-calcined material;

[0059] Step S2, mixing the pre-sintered material, tea polyphenol chitosan nanoparticles, soluble rosin-based polyimide and 1,3,5-triglycidyl-S-triazinetrione, and ball milling for 13 hours at a rotation speed of 280 rpm; pressing into a blank, and after secondary sintering, heat treatment to obtain a low-loss powder metallurgy core material; the pressing die pressure in step S2 is 350 MPa, and the pressure is maintained for 12 seconds.

[0060] The secondary sintering temperature in step S2 is 1330°C, the time is 5 hours, and the sintering vacuum is maintained at 0.03 Pa; the heat treatment in step S2 includes annealing and tempering; the tempering temperature is 300°C, and the time is 2 hours; the annealing includes two-stage annealing, the first stage annealing temperature is 230°C, and the insulation time is 45 minutes; the second stage annealing temperature is 800°C, and the insulation time is 1.5 hours.

[0061] Example 4

[0062] A low-loss powder metallurgy magnetic core material is made of the following components in percentage by weight: 0.25wt% rare earth powder, 4.5wt% manganese powder, 1.8wt% cobalt powder, 9wt% nickel powder, 1.3wt% chromium powder, 0.09wt% aluminum powder, 1.1wt% copper powder, 0.045wt% indium powder, 0.025wt% iridium powder, 0.0025wt% silver powder, 0.4wt% non-metallic component, 0.055wt% other metal component, 0.11wt% nano additive, and the balance is iron powder.

[0063] The nano additive is a mixture of nano ferroferric oxide, nano neodymium oxide, nano niobium oxide and nano yttrium oxide in a mass ratio of 4.5:0.5:1.1:1; the particle size of the nano additive is 70nm; the other metal component is bismuth powder; the non-metallic component is a mixture of Si, B and N in a mass ratio of 7.5:0.3:0.35; and the rare earth powder is Er powder.

[0064] The particle size of the rare earth powder is 1550 mesh; the particle size of the manganese powder is 1450 mesh; the particle size of the cobalt powder is 1550 mesh; the particle size of the nickel powder is 1900 mesh; the particle size of the chromium powder is 1550 mesh; the particle size of the aluminum powder is 1450 mesh; the particle size of the copper powder is 1350 mesh; the particle size of the indium powder is 1350 mesh; the particle size of the iridium powder is 1400 mesh; the particle size of the silver powder is 1250 mesh; the particle size of the non-metallic component is 1250 mesh; and the particle size of the other metal components is 1250 mesh.

[0065] The iron powder is carbonyl iron powder, and the carbon content of the carbonyl iron powder is less than 0.03wt.%; the particle size of the iron powder is 1500 meshes.

[0066] The preparation components of the low-loss powder metallurgy magnetic core material also include: 0.25wt% of tea polyphenol chitosan nanoparticles, 1.1wt% of soluble rosin-based polyimide, and 0.25wt% of 1,3,5-triglycidyl-S-triazinetrione; the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent with application number 201110037219.5; the soluble rosin-based polyimide is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN1102690414B.

[0067] A method for preparing the low-loss powder metallurgy magnetic core material comprises the following steps:

[0068] Step S1, mixing rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, copper powder, indium powder, iridium powder, silver powder, non-metallic components, other metal components, nano additives and iron powder according to weight percentage, and ball milling at a speed of 290 rpm for 4.5 hours; then pre-calcining at 740° C. for 2.5 hours under the protection of nitrogen atmosphere, and then heating to 955° C. and pre-calcining for 3.5 hours to obtain a pre-calcined material;

[0069] Step S2, mixing the pre-sintered material, tea polyphenol chitosan nanoparticles, soluble rosin-based polyimide and 1,3,5-triglycidyl-S-triazinetrione, and ball milling for 13 hours at a rotation speed of 290 rpm; pressing into a blank, and performing heat treatment after secondary sintering to obtain a low-loss powder metallurgy magnetic core material.

[0070] The pressing die pressure in step S2 is 410 MPa, and the pressure is maintained for 13 seconds; the secondary sintering temperature in step S2 is 1360° C., the time is 5.5 hours, and the sintering vacuum is maintained at 0.05 Pa.

[0071] The heat treatment in step S2 includes annealing and tempering; the tempering temperature is 340°C and the time is 2.5 hours; the annealing includes two-stage annealing, the first stage annealing temperature is 240°C and the insulation time is 55 minutes; the second stage annealing temperature is 840°C and the insulation time is 1.8 hours.

[0072] Example 5

[0073] A low-loss powder metallurgy magnetic core material is made of the following components in percentage by weight: 0.3wt% rare earth powder, 5wt% manganese powder, 2wt% cobalt powder, 10wt% nickel powder, 1.5wt% chromium powder, 0.1wt% aluminum powder, 1.2wt% copper powder, 0.05wt% indium powder, 0.03wt% iridium powder, 0.003wt% silver powder, 0.5wt% non-metallic component, 0.06wt% other metal component, 0.12wt% nano additive, and the balance is iron powder.

[0074] The nano additive is a mixture of nano ferrosoferric oxide, nano neodymium oxide, nano niobium oxide, and nano yttrium oxide in a mass ratio of 5:0.5:1.2:1; the particle size of the nano additive is 80nm; the other metal components are a mixture of titanium powder, vanadium powder, tantalum powder, bismuth powder, rhenium powder, beryllium powder, and cesium powder in a mass ratio of 1:1:2:1:0.5:0.8:0.2; the non-metallic component is a mixture of Si, B, and N in a mass ratio of 7.5:0.3:0.35; the rare earth powder is a mixture of Gd powder, Tb powder, Dy powder, and Er powder in a mass ratio of 1:2:3:1.

[0075] The particle size of the rare earth powder is 1600 mesh; the particle size of the manganese powder is 1500 mesh; the particle size of the cobalt powder is 1600 mesh; the particle size of the nickel powder is 2000 mesh; the particle size of the chromium powder is 1600 mesh; the particle size of the aluminum powder is 1500 mesh; the particle size of the copper powder is 1400 mesh; the particle size of the indium powder is 1400 mesh; the particle size of the iridium powder is 1500 mesh; the particle size of the silver powder is 1300 mesh; the particle size of the non-metallic component is 1300 mesh; and the particle size of the other metal components is 1300 mesh.

[0076] The iron powder is carbonyl iron powder, and the carbon content of the carbonyl iron powder is less than 0.03wt.%; the particle size of the iron powder is 1600 meshes.

[0077] The preparation components of the low-loss powder metallurgy magnetic core material also include: 0.3wt% of tea polyphenol chitosan nanoparticles, 1.2wt% of soluble rosin-based polyimide, and 0.3wt% of 1,3,5-triglycidyl-S-triazinetrione; the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent with application number 201110037219.5; the soluble rosin-based polyimide is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN1102690414B.

[0078] A method for preparing the low-loss powder metallurgy magnetic core material comprises the following steps:

[0079] Step S1, rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, copper powder, indium powder, iridium powder, silver powder, non-metallic components, other metal components, nano additives and iron powder are mixed according to weight percentage, and ball milled at a speed of 300 rpm for 5 hours; then pre-fired at 750° C. for 3 hours under the protection of nitrogen atmosphere, and then heated to 960° C. for pre-fired for 4 hours to obtain a pre-fired material;

[0080] Step S2, mixing the pre-sintered material, tea polyphenol chitosan nanoparticles, soluble rosin-based polyimide and 1,3,5-triglycidyl-S-triazinetrione, and ball milling at a rotation speed of 300 rpm for 15 hours; pressing into a blank, and after secondary sintering, heat treatment to obtain a low-loss powder metallurgy magnetic core material.

[0081] The pressing die pressure in step S2 is 420 MPa, and the pressure is maintained for 15 seconds; the secondary sintering temperature in step S2 is 1380° C., the time is 6 hours, and the sintering vacuum is maintained at 0.06 Pa.

[0082] The heat treatment in step S2 includes annealing and tempering; the tempering temperature is 350°C and the time is 3 hours; the annealing includes two-stage annealing, the first stage annealing temperature is 250°C and the insulation time is 65 minutes; the second stage annealing temperature is 850°C and the insulation time is 2 hours.

[0083] Comparative Example 1

[0084] A low-loss powder metallurgy magnetic core material and a preparation method thereof, which are substantially the same as those of Example 1, except that indium powder, iridium powder and nano-neodymium oxide are not added.

[0085] Comparative Example 2

[0086] A low-loss powder metallurgy magnetic core material and a preparation method thereof, which are substantially the same as those of Example 1, except that no silver powder, non-metallic components and tea polyphenol chitosan nanoparticles are added.

[0087] In order to further illustrate the unexpected positive technical effects achieved by the products of each embodiment of the present invention, relevant performance tests were carried out on the low-loss powder metallurgy core materials prepared in each example. The test results are shown in Table 1. The test method is as follows: the core loss Pcv of the core material at 100°C, 100kHz, and 200mT is measured using a BH hysteresis loop tester; the saturation magnetic flux density Bms at 100°C is measured.

[0088] Table 1

[0089] project <![CDATA[Core loss Pcv (kW / m 3 )]]> Saturation flux density Bms(mT) Example 1 280 1563 Example 2 273 1568 Example 3 264 1575 Example 4 259 1579 Example 5 256 1582 Comparative Example 1 318 1519 Comparative Example 2 335 1527

[0090] It can be seen from Table 1 that the low-loss powder metallurgy magnetic core material disclosed in the embodiment of the present invention has better comprehensive magnetic properties and lower magnetic core loss than the comparative product. The addition of indium powder, iridium powder, nano-neodymium oxide, silver powder, non-metallic components and tea polyphenol chitosan nanoparticles is beneficial to improving the above properties.

[0091] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as described above. However, any technician familiar with the profession can make some changes, modifications and evolutions of the technical content disclosed above without departing from the scope of the technical solution of the present invention, which are all equivalent embodiments of the present invention. At the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A low-loss powder metallurgy magnetic core material, characterized in that: The invention is made of the following components in percentage by weight: rare earth powder 0.1wt%-0.3wt%, manganese powder 3wt%-5wt%, cobalt powder 1wt%-2wt%, nickel powder 6wt%-10wt%, chromium powder 0.8wt%-1.5wt%, aluminum powder 0.05wt%-0.1wt%, copper powder 0.5wt%-1.2wt%, indium powder 0.03wt%-0.05wt%, iridium powder 0.01wt%-0.03wt%, silver powder 0.0 01wt%-0.003wt%, non-metallic components 0.1wt%-0.5wt%, other metal components 0.03wt%-0.06wt%, nano additives 0.08wt%-0.12wt%, and the balance is iron powder; the other metal components are at least one of titanium powder, vanadium powder, tantalum powder, bismuth powder, rhenium powder, beryllium powder, and cesium powder; the non-metallic components are Si, B, and N mixed in a mass ratio of (5-8):0.3:(0.1-0.4).

2. The low-loss powder metallurgy magnetic core material according to claim 1, characterized in that: The nano additive is a mixture of nano ferrosoferric oxide, nano neodymium oxide, nano niobium oxide and nano yttrium oxide in a mass ratio of (3-5):0.5:(0.8-1.2):1; the particle size of the nano additive is 10-80nm.

3. The low-loss powder metallurgy magnetic core material according to claim 1, characterized in that: The rare earth powder is at least one of Gd powder, Tb powder, Dy powder and Er powder.

4. The low-loss powder metallurgy magnetic core material according to claim 1, characterized in that: The particle size of the rare earth powder is 1300-1600 mesh; the particle size of the manganese powder is 1200-1500 mesh; the particle size of the cobalt powder is 1300-1600 mesh; the particle size of the nickel powder is 1500-2000 mesh; the particle size of the chromium powder is 1200-1600 mesh; the particle size of the aluminum powder is 1200-1500 mesh; the particle size of the copper powder is 1100-1400 mesh; the particle size of the indium powder is 1100-1400 mesh; the particle size of the iridium powder is 1200-1500 mesh; the particle size of the silver powder is 1000-1300 mesh; the particle size of the non-metallic component is 1000-1300 mesh; the particle size of the other metal components is 1000-1300 mesh.

5. The low-loss powder metallurgy magnetic core material according to claim 1, characterized in that: The iron powder is carbonyl iron powder, the carbon content of which is less than 0.03wt.%; and the particle size of the iron powder is 1200-1600 meshes.

6. The low-loss powder metallurgy magnetic core material according to claim 1, characterized in that: The preparation components of the low-loss powder metallurgy magnetic core material also include: 0.1wt%-0.3wt% of tea polyphenol chitosan nanoparticles, 0.8wt%-1.2wt% of soluble rosin-based polyimide, and 0.1wt%-0.3wt% of 1,3,5-triglycidyl-S-triazinetrione.

7. A method for preparing a low-loss powder metallurgy magnetic core material as claimed in claim 6, characterized in that: The steps include: Step S1, mixing rare earth powder, manganese powder, cobalt powder, nickel powder, chromium powder, aluminum powder, copper powder, indium powder, iridium powder, silver powder, non-metallic components, other metal components, nano additives and iron powder according to weight percentage, and ball milling at a speed of 250-300rpm for 2-5h; then pre-calcining at 700-750°C for 1-3h under nitrogen atmosphere protection, and then heating to 930-960°C for 2-4h to obtain a pre-calcined material; Step S2, mixing the pre-sintered material, tea polyphenol chitosan nanoparticles, soluble rosin-based polyimide and 1,3,5-triglycidyl-S-triazinetrione, and ball milling at a rotation speed of 250-300 rpm for 8-15 hours; pressing into a blank, and performing heat treatment after secondary sintering to obtain a low-loss powder metallurgy magnetic core material.

8. The method for preparing a low-loss powder metallurgy magnetic core material according to claim 7, characterized in that: The pressing die pressure in step S2 is 280-420MPa, and the pressure is maintained for 8-15s; the temperature of the secondary sintering in step S2 is 1230-1380°C, the time is 4-6h, and the sintering vacuum is maintained at 0.01-0.06Pa; the heat treatment in step S2 includes annealing and tempering; the temperature of the tempering is 210°C-350°C, and the time is 1-3 hours; the annealing includes two-stage annealing, the first stage annealing temperature is 190-250°C, and the heat preservation is 25-65min; the second stage annealing temperature is 750-850°C, and the heat preservation is 1-2h.

Citation Information

Patent Citations

  • Preparation method and application of tea polyphenol chitosan nanoparticles

    CN102631472A

  • A manganese-zinc ferrite core with high saturation magnetic flux density and its preparation method

    CN110335732B

  • Magnetic material and method for producing same

    CN103081035A

  • Magnetic material

    CN103430248A